2009
DOI: 10.1111/j.1600-0501.2008.01690.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of repeated torque/mechanical loading cycles on two different abutment types in implants with internal tapered connections: an in vitro study

Abstract: Torque loss was higher in groups 4a and 2 (over 30% loss), followed by group 1 (10.5% loss), group 3 (5.4% loss) and group 4b (39% torque gain). All the results were significantly different. As the number of insertion/removal cycles increased, removal torques tended to be lower. It was concluded that mechanical loading increased removal torque of loaded abutments in comparison with unloaded abutments, and removal torque values tended to decrease as the number of insertion/removal cycles increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 26 publications
(39 reference statements)
1
30
0
Order By: Relevance
“…Six trials studied changes in preload, specifically tightening torque loss or gain of the implant–abutment system . The principle objectives were to assess the changes in torque after initial tightening and how this was influenced by the following: (1) Increased/decreased initial tightening torque, (2) Repeated tightening and removal cycles, and (3) Fatigue loading . Two investigations addressed seal performance, whereas others were focused on stress/load performance, particularly dealing with load fatigue performance of the implant–abutment unit .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Six trials studied changes in preload, specifically tightening torque loss or gain of the implant–abutment system . The principle objectives were to assess the changes in torque after initial tightening and how this was influenced by the following: (1) Increased/decreased initial tightening torque, (2) Repeated tightening and removal cycles, and (3) Fatigue loading . Two investigations addressed seal performance, whereas others were focused on stress/load performance, particularly dealing with load fatigue performance of the implant–abutment unit .…”
Section: Resultsmentioning
confidence: 99%
“…Torque loss was also measured as a result of multiple consecutive closures using different implant–abutment connections. It was shown that when tightening and removal cycles were increased in number, there were concomitant reductions in the torque forces required for removal of the abutment . Using this approach, Weiss et al documented significantly higher maintenance of torque values for both conical frictional or interlocking elements …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The separation and retrieval of a fractured abutment wedged inside the implant require direct access and delicate manipulation to prevent damage to the internal part of the implant. 3,13,17,18 Despite the clinically challenging situation, management of the fractured abutment has not been clearly established. [9][10][11][12][13] Common approaches for retrieving the fractured fragment are the use of an explorer, spoon excavator, or long sharp-ended ultrasonic instruments.…”
mentioning
confidence: 99%
“…Preloading the abutment screw and occlusal loading could wedge the fractured abutment into the implant and require high pull-out force. 16,17 Saliva, blood, and the limited visibility of the dental implant make it difficult to access. The separation and retrieval of a fractured abutment wedged inside the implant require direct access and delicate manipulation to prevent damage to the internal part of the implant.…”
mentioning
confidence: 99%